Implications of circulating irisin and Fabp4 levels in patients with polycystic ovary syndrome. (2nd October 2016) - Abali, Remzi; Temel Yuksel, Ilkbal; Yuksel, Mehmet Aytac; Bulut, Berk; Imamoglu, Metehan; Emirdar, Volkan; Unal, Fehmi; Guzel, Savas; Celik, Cem
Abstract: The aim of the study was to evaluate the fatty acid-binding protein-4 (FABP4) and irisin concentrations in women with polycystic ovary syndrome (PCOS). Forty-nine women with PCOS, diagnosed according to Rotterdam criteria and 39 healthy women matched for body mass index (BMI) and age. Serum irisin and plasma FABP4 concentrations were measured in both groups. The association of irisin and FABP4 concentrations with metabolic parameters were also tested. Women with PCOS had significantly lower mean serum irisin concentrations than control subjects (158.5 ± 123.3 versus 222.9 ± 152.2 ng/ml, p < 0.05). Concentrations of FABP4 in PCOS and control groups were not significantly different (10.5 ± 4.4 versus 10.9 ± 4.2 ng/ml, p > 0.05). FABP4 concentrations were correlated with BMI, waist–hip ratio (WHR) and HOMA-IR ( r = 0.57, p = 0.001; r = 0.26, p = 0.03; r = 0.26, p = 0.03, respectively). No associations between irisin and all the others parameters except serum levels of LH were found. Serum irisin concentrations of women with PCOS were lower compared to the controls. Moreover, there were no difference in plasma FABP4 concentrations between women with PCOS and controls.